Address Presenting the Sixth Annual Report - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, spoke about the substantial growth of Bank activities, totaling 21 loans extended to 11 different countries in fiscal year 1951. Technical assistance for preparation and execution of loan projects is increasingly significant to Bank lending operations. He reported on completion of economic survey missions to Turkey, Guatemala, Cuba, and Uruguay and progress with five others. He noted that the Bank broadened its base in the private capital markets which provide the bulk of the loan funds, including public offerings of bonds in the United Kingdom and Switzerland. The Bank expects to issue bonds in the American market more regularly. He warned against overlending to countries that are not ready to put the capital to work. He reacted to proposals for an international finance corporation to stimulate private enterprise and to make equity investments. He reiterated the fundamental principles of development. He concluded by saying that the Bank's objective is to protect and enlarge the freedom of the individual, and that is surely worth all the energy the Bank can devote to its achievement.